Clinical cancer chemoprevention: From the hepatitis B virus (HBV) vaccine to the human papillomavirus (HPV) vaccine - Horng-Jyh Tsai (Elsevier, 2015)
Approximately 2 million new cancer cases are attributed to infectious agents each year worldwide. Vaccines for the hepatitis B virus (HBV), a risk factor of hepatocellular cancer, and human papillomavirus (HPV), a risk factor of cervical cancer, are considered major successes in clinical chemoprevention of cancer. In Taiwan, the first evidence of cancer prevention through vaccinations was provided by HBV vaccination data in infants. The Taiwanese HBV vaccination program has since become a model immunization schedule for newborns worldwide. Persistent infection with high-risk HPV is generally accepted as prerequisite for cervical cancer diagnosis; however, cervical cancer is a rare complication of HPV infections. This is due to the fact that such infections tend to be transient. The safety and efficacy of both available HPV quadrivalent vaccine and bivalent vaccine are not in doubt at the present time. Until a human cytomegalovirus (CMV) vaccine becomes available, simple hygienic practices, such as hand washing, can prevent CMV infection both before and during pregnancy. Each country should establish her official guidelines regarding which vaccines should be used to treat various conditions, the target population (i.e., universal or limited to a selected population), and the immunization schedules. After a vaccine is recommended, decisions regarding reimbursement by the public health care fund are evaluated. The guidelines become part of the immunization schedule, which is updated annually and published in the official bulletin. In conclusion, both HBV and HPV vaccines are considered major successes in the chemoprevention of cancer.